In vivo anesthetic effect and mechanism of action of active compounds from Alpinia galanga oil on Cyprinus carpio (koi carp) - Nattakanwadee Khumpirapang (2018)
© 2018 In the present study, three active compounds of Alpinia galanga oil (AGO); 1,8-cineole (37.43%), 4-allylphenyl acetate (25.97%), and methyl eugenol (5.07%) were investigated for anesthetic effect on Cyprinus carpio (koi carp) and their mechanism of action. The anesthetic effect was evaluated by determining the induction time that the fish needed to reach the surgical stage of anesthesia and subsequent recovery time. Among the three test compounds, methyl eugenol showed the shortest induction time and longest recovery time. The induction times of 4-allylphenyl acetate were longer and the recovery times were shorter than 1,8- cineole. For the mechanism of action, the compounds were investigated by computational docking into the benzodiazepine (BZD) site of the γ-aminobutyric acid type A (GABAA) receptor complex model. Ligand-protein docking interaction, i.e., binding energy (ΔGbind) and inhibitory constant (Ki), were calculated. The result of the computational prediction was related to the experimental anesthetic activity, where methyl eugenol showed the lowest ΔGbindof −6.10 kcal mol−1and Kiof 33.84 μM, followed by 4-allylphenyl acetate (with ΔGbindof −5.67 kcal mol−1and Kiof 70.30 μM), and 1,8-cineole (with ΔGbindof −5.39 kcal mol−1and Kiof 112.40 μM). To this end, a comparison of recovery time of the anesthetized fish using flumazenil, a BZD antagonist, was carried out. The fish exposed to all tested compounds resulted a faster recovery in the water tank with flumazenil than that without flumazenil, confirming the receptor binding site of these three compounds are GABAAreceptor interaction. It is concluded that the anesthetic effect of AGO on koi carp is according to the three main active compounds; 1,8-cineole, 4-allylphenyl acetate, and methyl eugenol. Moreover, the mechanism of anesthetic action of these compounds is exerting GABAAreceptor interaction via the BZD-binding site.